Ghana : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper and Annual Progress Report on Implementation of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2006)
Executive Directors believe that the Growth and Poverty Reduction Strategy (GPRS) outlines a comprehensive framework for growth and poverty reduction in Ghana. The GPRS II rightly emphasizes private sector-led growth as key to broadening the country's economic base. The GPRS II will benefit from analyzing the risks to the strategy such as inability to implement planed structural reforms, exogenous shocks and domestic factors, fiduciary weaknesses, and capacity limitations. A comprehensive macroeconomic framework that is consistent with the medium-term fiscal framework and growth assumptions is required.